ELECTROCHEMICAL REDUCTION OF CO2 USE PB-SN IN BUBBLE REACTORS - Nurul Aulia Irawan, Silmia
Many human activities are still depending on fossil fuels. The use of fossil fuels greatly contributes to the increasing concentration of CO2 in the atmosphere, which lead to more complicated environmental problems. Various efforts have been made to reduce CO2 concentration in the atmosphere, from reducing emissions to the technology to capture and store CO2. Various studies have also been done to convert CO2 into other value-added compounds. One such technology is the conversion of CO2 using an electrochemical reduction process into another compound, namely formic acid. Formic acid is widely used as a raw material for various chemical processes in industry. The electrochemical reduction of CO2 was carried out using Pb-Sn cathode and Pt-Ir anode. 0,5 M KHCO3 is used as catholyte and 0,1 M H2SO4 is used as anolyte. The sparger’s type, length of the cathode, and distance of the cathode to sparger were varied. Aqueous products from the experiment were analyzed with High Performance Liquid Chromatography (HPLC), gas products with Gas Chromatography (GC), and the cathode’s morphology with Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD). Bubble stone sparger with bubble sizes 6.18 and 3.26 times smaller, produces 29.23% and 15.23% higher current efficiency, the formic acid yield is 50.70% and 28.21% higher than the other sparger types at the same voltage. Shorter distance from cathode to the sparger (0.5 cm) results in higher current efficiency and formic acid yield in most of the experiment. Shorter cathode length (2.5 cm) also results in higher current efficiency and formic acid yield in all variations of the experiment. The best formic acid results with a yield of 0.122% and a current efficiency of 11.60% were obtained with bubble stone, 2,5 cm cathode length, 0.5 cm cathode distance from sparger, and operating voltage of 6 Volts.